In times of crisis : perspectives and challenges of the 21st century - Diallo, Mbaye Fall; Kaswengi, Joseph (Economic issues, problems and perspectives series., 2018)
The present book concentrates on financial crises across distinct disciplines. It gathers a collective work on crisis situations in different domains and various contexts. The book includes works with qualitative and quantitative approaches, case studies, and empirical and conceptual perspectives--Back cover.